Analisis Nilai Sosial dalam Iklan Gojek Edisi “Jangan Sepelekan Kekuatan Jempol” di Youtube - Wisnu Dwi Yuliyanto; Rahmawati Zulfiningrum (Journal on Education, 2023)
The phenomenon of decreasing social values in the society, as depicted in the Gojek ad campaign "Don't Underestimate the Power of a Thumb," illustrates social values that can inspire the community to use a thumb as a symbol of appreciation for valuable but forgotten contributions. The goal of this research was to understand the social values present in the ad and then analyze the audience's understanding of those social values. This research is a descriptive qualitative study using the interpretive paradigm with Roland Barthes' semiotics theory. The data collection methods used were observation and interview. Three types of social values were found: Material Value, Vital Value, and Spiritual Value. The Roland Barthes semiotic analysis revealed 17 scenes in the ad with broad meanings. The results of the research showed the audience's understanding of the social values in the ad as follows: a) increasing the audience's awareness of concern in their surroundings, b) providing education and literacy to the audience on social media platforms, c) improving the economic quality of life, particularly for small merchants and lower-middle-class drivers.